Can productivity and profitability be enhanced in intensively managed cereal systems while reducing the environmental footprint of production? Assessing sustainable intensification options in the breadbasket of India - Jat, H.S. (2020)
Crop residues and animal dung can contribute a significant portion to the biomass available for conversion to biofuels in Zimbabwe. This paper will extend a quantitative methodology involving the use of probability distributions to rigorously address uncertainty in the quantification of this biomass. The results of 100 000 Monte Carlo simulations using Palisade’s @Risk tool indicates the following at a 90% confidence interval: 2.55-5.50 million Mg/yr. of crop residue and 2.99-4.99 million Mg/yr. of dung is generated. The total exploitable energy was estimated at an annual mean of 26.6 and 16.9 million GJ for crop residue and dung Can productivity and profitability be enhanced in intensively managed cereal systems while reducing the environmental footprint of production? Assessing sustainable intensification options in the breadbasket of India.